ANALISIS KINERJA KEUANGAN DAERAH DI KOTA MOJOKERTO PADA MASA PANDEMI COVID-19 TAHUN 2020-2021 - Meylinda Thirta Arlina; Pujianto Pujianto (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2023)
This study aims to analyze the Financial Performance of the Mojokerto City Government by using the Fiscal Decentralization Degree Ratio, Fiscal Decentralization Ratio, Regional Financial Independence Ratio, PAD Effectiveness Ratio, Regional Financial Efficiency Ratio and Harmony Ratio. This research use desciptive qualitative approach. The results of the analysis show that the Financial Performance of the Mojokerto City BPKPD as seen from (1) the Degree Ratio of Fiscal Decentralization can be categorized as Very Good, ​​(2) The Regional Financial Independence Ratio is classified as high and the relationship pattern includes the Delegative relationship pattern. (3) The PAD Effectiveness Ratio is known that the financial effectiveness of the Mojokerto City BPKPD is quite effective, (4) Mojokerto City Regional Financial Efficiency Ratio can be said to be Inefficient, (5) Regional Financial Harmony Ratio of Mojokerto City BPKPD in financial analysis regions are harmonious.